Fetal Development of Fasciae around the Arm and Thigh Muscles: A Study Using Late Stage Fetuses. Issue 7 (30th March 2018) - Cho, Kwang Ho; Jang, Hyung Suk; Abe, Hiroshi; Yamamoto, Masahito; Murakami, Gen; Shibata, Shunichi
ABSTRACT: To obtain a better understanding of multi‐laminar deep fascia covering skeletal muscles, we examined nondecalcified histological sections of the arm and thigh of 20 human fetuses aged 25–33 weeks. Morphologies of the fasciae varied between sites and specimens, but the initial morphology was most likely to be a thin and loose sheet on the external surface of the muscles (fascia‐1 or F1). When the F1 became wavy, thick and tight, it was detached from the muscle surface. Beneath the F1, the second lamina of fascia (F2) appeared on the muscle surface and it was also detached. In this manner at 25–33 weeks' gestation, fasciae covering the triceps and vastus lateralis muscles had a three‐layered configuration (F1, F2, and F3). Due to significant individual variations, this process was not correlated to the ages and sizes of specimens. Muscle contractions might facilitate the detachment. In these muscles, the intramuscular tendon joined the F2 or F3 and the latter became thick and aponeurotic. Along the finally developed lamina, muscle fibers carried a desmin‐positive spot for insertion. Increased laminae were accompanied by a reduced number of CD68‐positive macrophages and, nerves were absent, near the developing fascia. In contrast to skin ligaments or superficial fasciae showing de novo development in loose tissue, a deep or muscle‐covering fascia seemed to originate from the skeletal muscle itself at the surface, and this process was repeated to produce multi‐layered fascia. Depending on sites, collagen fibers were added by the intramuscular tendon. Anat Rec, 301:1235–1243, 2018. © 2018 Wiley Periodicals, Inc.